Knowledge and Practices of Child Protection among the School Health Nurses of Nepal - Chapagain, R. H.; Adhikari, S.; Pandey, A.; Sharma, S.; Pokhrel, S.; Devkota, N.; Shrestha, N. J.; Upadhaya, D.; Acharay, J.; Dharel, M. (Kathmandu University Medical Journal, 2021)
Background Child protection is burning issues in developing countries including Nepal. Child protection is one of the key works of the school health nurses.Objective To find out about the existing knowledge and practices of child protection among the school health nurses.Method This descriptive cross-sectional study was conducted among 130 school health nurses working in different schools throughout Nepal. The participants were selected using purposive sampling technique and were invited to participate via various online networks. Self-administered questionnaire was used to collect data. Duration of data collection was 20 December 2020 to 10 February 2021. Descriptive statistics was used to analyze and interpret the data.Result Among the 130 Participants, 88.5% belonged to less than 29 years age group and 67.7% had Proficiency Certificate Level in Nursing education. None of them has received training related to child protection recognition and response and 90.8% had work experience of less than 5 years. Eighty percent and 96.9% participants had knowledge regarding the meaning of child right and child abuse respectively. But 45.4% had knowledge on meaning of child neglect; 53.1% and 72.3% had the knowledge of physical abuse and noncontact sexual abuse respectively. Majority (86.9%) of the participants reported as relatives were the abuser and 63.8% replied as home is the common place for abuse. Similarly, 85.4% had received the information regarding child protection via television radio and newspaper. Only 36.1% has already been involved in child protection. The participants who went to local government (Palika), police and Non-government Organizations for coordination for child right issues were 9(19.1%), 7(14.8%) and 8(17.0%) respectively.Conclusion Most of the school health nurses are young without having experience of childhood abuse and received any child protection training before joining the job. They have good knowledge of child right, physical, sexual abuse except child neglect and existing legal arrangements. There is gap in knowledge and practice.